Caregiver Depression and Early Child Development: A Mixed-Methods Study From Rural China - Yue, Ai; Gao, Jiaqi; Yang, Meredith; Swinnen, Lena; Medina, Alexis; Rozelle, Scott (Frontiers in Psychology, 2018)
Half of rural toddlers aged 0–3 years in China's Qinling Mountainous region are cognitively delayed. While recent studies have linked poor child development measures to the absence of positive parenting behaviors, much less is known about the role that caregiver depression might play in shaping child development. In this paper, a mixed methods analysis is used to explore the prevalence of depression; measure the association between caregiver depression and children's developmental delays, correlates of depression, and the potential reasons for caregiver depression among women in rural China. The analysis brings together results from a large-scale survey of 1,787 caregivers across 118 villages in one northwestern province, as well as information from in-depth interviews with 55 female caregivers from these same study sites. Participants were asked to respond to the Depression, Anxiety and Stress Scale-21 (DASS-21) as well as a scale to measure children's social-emotional development, the Ages and Stages Questionnaire: Social-Emotional (ASQ-SE). We also administered a test of early childhood development, the Bayley Scales of Infant and Toddler Development (BSID-III), to all of the study household's infants and toddlers. The results show that the prevalence of depression may be as high as 23.5 percent among all female caregivers (defined as scoring in the mild or higher category of the DASS-21). Grandmothers have higher prevalence of depression than mother caregivers (p < 0.01). Caregiver depression also is significantly associated with a 0.53 SD worsening of children's social-emotional development (p < 0.01) and a 0.12 SD decrease in children's language development (p < 0.05). Our qualitative findings reveal six predominant reasons for caregiver depression: lack of social support from family and friends; the burden of caregiving; lack of control and agency within the household; within-family conflict; poverty; the perception of material wealth as a measure of self-worth. Our findings show a serious lack of understanding of mental health issues among rural women, and suggest that rural communities could benefit greatly from an educational program concerning mental health and its influence on child development. Our findings confirm the need for a comprehensive approach toward rural health, with particular attention paid to mental health awareness and support to elderly caregivers.